PO DOŚWIADCZENIACH PISANIA PRACY MAGISTERSKIEJ W OBLICZU PRACY NAD ROZPRAWĄ DOKTORSKĄ. ESEJ O MOICH ZMAGANIACH Z WARSZTATEM BADAWCZYM - Szafrański, Mateusz (Rocznik Pedagogiczny, 2018)
This article presents experiences associated with writing my master’s thesis and designing research to my doctoral dissertation. In this text I indicate determinants that shape my research addescence is favourable to conducting reliable research projects. In both cases research sets in pedagogy of people with intellectual disabilities (oligophrenopedagogy) – a detailed science of special pedagogy that deals with an individual and social life of a person with intellectual disabilities.